Embryonic proteins in somatic embryos of carrot - Sung, Z. R. (1981)
The translational profile of cultured carrot cells (callus) was compared with that of the somatic embryos derived from them. The two tissues synthesize almost the same number and kinds of polypeptides except for two “embryonic” proteins. These were found in the somatic embryos but were nearly undetectable in the callus. Both embryo development and the production of embryonic proteins were induced by the same trigger (transfer of the callus to fresh medium) and were suppressed by the same factor (2,4-dichlorophenoxyacetic acid). But the appearance and disappearance of the proteins occurred several days prior to embryo formation and to the conversion of embryo to callus, respectively. Carrot cell lines incapable of embryogenesis could not synthesize the embryonic proteins. These findings indicate that the embryonic proteins play a key role in the process of embryo development. The function of these proteins is presently unknown; however, they can serve as early developmental markers for studying the mechanisms underlying somatic embryogeny in plants.